An experimental-based model for the assessment of the mechanical properties of road pavements using ground-penetrating radar. (20th March 2018) - Tosti, Fabio; Bianchini Ciampoli, Luca; D'Amico, Fabrizio; Alani, Amir M.; Benedetto, Andrea
Highlights: Non-destructive assessment of a road flexible pavement. Development of an experimental-based model for road pavement stiffness assessment. Integration and modelling of data from GPR (2 GHz horn antenna) and LFWD equipment. Development of a time-efficient methodology (quantitative and qualitative modelling). Abstract: This work proposes an experimental-based model for the assessment of the stiffness of a road flexible pavement using ground-penetrating radar (GPR – 2 GHz horn antenna) and light falling weight deflectometer (LFWD) non-destructive testing (NDT) methods. It is known that the identification of early decay and loss of bearing capacity is a major challenge for effective maintenance of roads and the implementation of pavement management systems (PMSs). To this effect, a time-efficient methodology based on quantitative and qualitative modelling of road stiffness is developed. The viability of using a GPR system in combination with LFWD equipment is also proven.